PERBANDINGAN BUSI STANDAR DENGAN BUSI PLATINUM PADA SEPEDA MOTOR HONDA CB 150 TERHADAP POWER DAN KONSUMSI BAHA BAKAR DENGAN VARIASI CELAH BUSI - Budiyono, Budiyono; Mahfudin, Ains Eka (Universitas Muhammadiyah Pekajangan Pekalongan, 2018)
ABSTRACT This thesis aims to compare between standard and spark plugs platinum on a motorcycle Honda CB150R to power and fuel consumption. To find out which one is better spark plug to the desired engine performance. The research process including standard and platinum spark plugs installed with a gap of 0.40, 0.70, 0.90 mm dynotest then performed to determine the power produced from each standard and platinum spark plug gap. Then to find out the results of the research of fuel consumption is done by replacing the standard plug and platinum with a gap of 0.40, 0.70, 0.90 mm and tested in a way to fill the fuel into the tank with a volume of 1000 ml and then turn the engine with over 5 min at engine speed of 5000 rpm constant on each of the spark plugs, then record the results of testing of the fuel. The results of the study can be determined by comparing the standard plug and platinum spark plugs and spark plug gap of 0.40, 0.70, 0.90 mm Which better engine performance and fuel consumption more efficient. Keywords: Spark Plug, Test, Honda CB 150 R..